Evaluation The Performance efficiency of the general company for lather Industries (a practical study) - حداد, حامد عبيد (Journal of Economics and Administrative Sciences, 2014)
The performa of evaluation process is a process that should be carried out by all industrial management in order to stand on aspects of development or underdevelopment of the various departments and activities in its industrial project for the purpose of identifying obstacles and find out the causes and then avoid them quickly. And intended to rectify the performance evaluation of the  activities of  industrial project  or economic union by measuring the results achieved within a specific operational process and compare it to what is already targeted, and often the time for comparison of one year.The process of performance evaluation depends upon several criteria and indicators within the various economic units, and can be defined the  standards and performance indicators as (semantic that indicate information management health paths taken, they are a means of effective control, it is also a way of planning where supply scheme with all necessary information about the extent and effectiveness of any plan of multiple plans even done the necessary amendment and improve performance).        There are many indicators and criteria to be used in measuring the performance efficiency in industrial projects, but the study dealt with the indicators that fit existing activities in the company placed search during the study period. The company has faced many problems and obstacles that prevented the achievement of productivity plans, which led to low capacity utilization planned, especially after 2002.it faces  huge forfeitures that  are estimated billion Iraqi  dinars since 2003 and the following years, a mtler that makes it to loan from ministry of Finance to pay the salaries of its officials and complete its other business.